All Days 2009
DOI: 10.4043/20124-ms
|View full text |Cite
|
Sign up to set email alerts
|

From Turbidites to Carbonates: Breaking Paradigms in Deep Waters

Abstract: In the beginning of exploration of the Brazilian Continental Shelf, Petrobras focused its exploratory efforts on deltaic sequences and a discovery was done in the offshore extension of the Sergipe-Alagoas Basin. The important discoveries in turbidites in Campos Basin in the middle 1970's, pointed out these siliciclastic reservoirs as the main exploratory targets in the Brazilian continental margin. Applying well defined geological models, along with true seismic amplitude and in-house wavelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Can the carbonate factory produce bench-like margins that are seismically resolvable, and if so what facies would be expected at such margins and their adjacent slopes? Carminatti et al (2008Carminatti et al ( , 2009) refer to seismic-scale prograding clinoforms from the microbialite carbonates in the Santos Basin. Could microbial buildups generate 'shelf-edge' reservoirs comparable to those hosted in marine reefs, or lacustrine factories generate shoal belt grainstones comparable to marine 'shelf-edge' sandbodies?…”
Section: Lacustrine Carbonate Facies Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Can the carbonate factory produce bench-like margins that are seismically resolvable, and if so what facies would be expected at such margins and their adjacent slopes? Carminatti et al (2008Carminatti et al ( , 2009) refer to seismic-scale prograding clinoforms from the microbialite carbonates in the Santos Basin. Could microbial buildups generate 'shelf-edge' reservoirs comparable to those hosted in marine reefs, or lacustrine factories generate shoal belt grainstones comparable to marine 'shelf-edge' sandbodies?…”
Section: Lacustrine Carbonate Facies Modelsmentioning
confidence: 98%
“…The discovery of 'microbialite' carbonate reservoirs in the South Atlantic rift-sag lacustrine basins (Carminatti et al 2008(Carminatti et al , 2009Nakano et al 2009) has generated considerable interest and is even referred to frequently in advertisements on Brazilian television. However, virtually no detailed scientific publications have appeared on these carbonates.…”
mentioning
confidence: 98%
“…Abrahão and Warme, 1990;McArgue, 1990;Thomson et al, 2015). Coquina reservoirs are Mollusk-dominated grainstones to rudstones that are interpreted to have been deposited in non-marine lacustrine environments (Carminatti et al, 2009) even though evidences of marine incursions have been reported onshore within the coquina interval in the Sergipe-Alagoas Basin (Thomson et al, 2015).…”
Section: Lower Cretaceous Pre-salt Lacustrine Carbonate Reservoirs (Omentioning
confidence: 99%
“…The presalt sequence can be categorized into three phases: lower synrift, upper synrift, and sag sequences (Cainelli, 1999;Carminatti et al, 2009). Synrift sequences display numerous extensional faults (Mann, 2013).…”
Section: Geologic Motivationmentioning
confidence: 99%